PENGARUH ENDORSMENT RACHEL VENYA TERHADAP DAYA BELI FOLLOWERS PADA PRODUK PAKAIAN WANITA MELALUI SOSIAL MEDIA INSTAGRAM - Abdul Gani Pulungan; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The social media Instagram is a new media that is very popular with Indonesians. The Instagram @ Rachelvenya social media as an example of an account that is considered viral and is followed by millions of teenagers in Indonesia can influence the activities, interests, opinions and lifestyle of its users. Her followers often pay attention to Rachel Venya's fashion style, be it her personal clothes or her endors' clothes, and are always the center of attention. The purpose of this study was to determine the effect of Rachel Venya's endorsement on Instagram social media on her followers on women's clothing products using the Stimulus Response (S-R) theory as the basis.This type of research is explanative research with a quantitative approach. The data collection technique in this study used a questionnaire with a sample size of 100 respondents who were taken using the Slovin formula with random sampling techniques. The data analysis method used is multiple linear regression analysis, t test, F test and coefficient of determination with the help of SPSS version 24.The results of hypothesis testing in this study using multiple linear regression analysis showed the results of endorsment (X1) = (4,915), while the results of Social Media (X2) = (4.185) with T-table 100 = (1.984). It is known that X1> T-table (4,915> 1,984) while X2> T-table (4,185> 1,984), it can be concluded that each independent variable affects the dependent variable because t-count> t-table. Then H0 is rejected and H1 is accepted. It is known that F count (43,721)> F table (3,06). This means that the independent variables (endorsment and social media) together have an effect on the dependent variable (purchasing power). Then H0 is rejected and H1 is accepted. From the results of this study also obtained r square of 0.474 which indicates that the variable purchasing power is affected by 47.4%, while the remaining 52.6% is influenced by other variables not included in this study.